Mapping the Research Task for the Construction of a Federal System for Classifying the Nation's Rural School Districts - E. Robert Stephens (Journal of Research in Rural Education, 1992)
The current efforts underway at the federal level to better understand the diversity in the public school universe must acknowledge the increasingly apparent differences in the nation's large rural-school component. The research task necessary to achieve this objective is formidable and includes addressing a large number of definitional, conceptual, methodological, and policy-application issues. Each of these four interrelated clusters of research issues is further broken down into a series of lead questions in order to facilitate the development of the proposed itinerary for mapping the research task required to construct a meaningful classification system.